PENGARUH pH LARUTAN DAN UKURAN PARTIKEL ABU SEKAM PADI TERHADAP PENURUNAN KADAR CONGO RED - Tien Setyaningtyas; Uyi Sulaeman (Universitas Jenderal Soedirman, 2007)
Rice husk used as a raw material to produce the rice husk ash. The purpose of this research were to determine the optimum contact time and maximum pH of congo red adsorption by rice husk ash, to find out the influence of particle size to adsorption The rice husk was washed, then soaked in HCl 3.84 M to remove mineral impurities, and it was dried and heated for four hours at the temperature 6000 C. The yield gained from this research is 23.44%. Optimum contact time started at after five minutes and maximum pH is six for the tree mention particle sizes 50, 100 and 140 mesh. Particle size didn’t give any significant effect to adsorption process with percent decreasing of congo red is 84.97 %, 90.39 %, 89.32 % respectively.